Veteran's Village and Green Hall, 1955 - Unidentified photographer (Colorado State University. Libraries, 1955)
Aerial view of Green Hall and the Veteran's Village on CSU's campus, 1955.
Not digitized by CSUL Digital Services.
Keywords: veterans; Quonset hut; Green Hall; temporary housing; military; GI Bill